PENGARUH METODE EKSPERIMEN TERHADAP KEMAMPUAN BERPIKIR KRITIS ILMU PENGETAHUAN ALAM DAN SOSIAL - Diko Nasrul Fitama; Firma Andrian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low critical thinking ability of students poses a challenge in solving everyday life problems. This issue should ideally be addressed, considering that critical thinking is a crucial part of 21st-century skills that students must possess. This research aims to determine the effect of the experimental method on critical thinking skills in IPAS (Science and Social Studies). The type of research used is quasi-experimental with a quantitative approach. The research design is a two-group pretest-posttest design. The population in this study consists of all fourth-grade students, totaling 49 students, while the sample is divided into two groups: 25 students in the experimental class and 24 students in the control class. The sampling technique used is simple random sampling. Data collection techniques include tests, observation, and documentation. The research instruments used are essay test sheets, observation sheets, and checklist sheets. The data analysis technique employed is inferential statistics using the independent sample t-test and normalized N-gain test. The findings based on the independent sample t test that has been carried out obtained a sig. (2-tailed) value of 0.034 < α = 0.05 then H1 is accepted and H0 is rejected, which means that the use of experimental methods affects the critical thinking skills of IPAS. Furthermore, the normalised N-gain test in the experimental class obtained a value of 0.39, which means that there was an increase in the critical thinking ability of IPAS with a moderate category, while the control class obtained a value of 0.18, which means that there was an increase in the critical thinking ability of IPAS with a low category.